Perancangan Sistem Enkripsi Pesan Teks Menggunakan Enkripsi RSA dan Caesar Cipher - Wisnawa, I Nyoman Arista; Widiartha, I Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 3 (2025): JNATIA Vol. 3, No. 3, Mei 2025, 2025)
The development of communication methods has changed a lot in the current digital era, people who initially communicated face-to-face or through a mail are starting to communicating through the internet. Nowadays, people more often exchange information on social media. The increasingly widespread internet infrastructure makes it easier for people to access social media without being limited by place or time. The vast digital world certainly requires a way to secure the information circulating through the internet. The vulnerability of data on the internet to hacking and leaks makes it important to have strong security measures to protect sensitive data from unauthorized access. Encryption plays an important role in overcoming this problem. Encryption is the process of changing text data into another form that cannot be understood without knowing the correct decryption key. This research applies two different encryption methods to secure text data, utilizing a combination of the Caesar cipher and RSA algorithms to strengthen data security. The proposed system offers enhanced protection against potential security breaches, ensuring data confidentiality and integrity.